RADA’AH PERSPEKTIF AL-QUR’AN SURAT AL-BAQARAH AYAT 233: (Sudut Pandang Ilmu Kesehatan) - Subaini, Siti Iraini; Arisandy, Danil Putra (BASHA'IR: JURNAL STUDI AL-QUR'AN DAN TAFSIR, 2022)
This study aims to determine the urgency of rada'ah in QS. al-Baqarah: 233 from the point of view of health sciences. Researchers chose to use research methods that are field studies (field research), the type of research used is qualitative. Data collection techniques using observation, interviews and literature searches. The results of this study are that there are two urgencies of breastfeeding, namely for the baby and for the mother. For babies, research by child health experts says that babies who receive breast milk can reduce infant mortality rates caused by digestive disorders such as diarrhea and pneumonia. Meanwhile, babies who do not receive breast milk only drink formula milk very often suffer from stunting, so it is increasingly clear that breast milk is rich in nutrients that are needed by babies. As for mothers, the benefits of breastfeeding for mothers are preventing bleeding, reducing breast cancer, shrinking the uterus as it was before, and helping weight loss more quickly.